Effect of remineralizer on soil biological quality - Rosalen K.* (2024)
© Plant Science and Biodiversity Centre, Slovak Academy of Sciences (SAS), Institute of Zoology, Slovak Academy of Sciences (SAS), Institute of Molecular Biology, Slovak Academy of Sciences (SAS) 2024.The use of remineralizers has been highlighted as a viable option for alternative fertilizer sources. However, it is necessary to study the impacts of its use on the biological quality of the soil. The objective of this study was to evaluate the effect of the remineralizer on the diversity of the edaphic fauna. The research was carried out in a randomized block design, with four replications and the following treatments: T0: control; T1: 100% of N-P-K; T2: Fertilization only with remineralizer; T3: 75% of N-P-K + remineralizer; T4: 75% of N-P-K + remineralizer + Azospirillum spp.; T5: 75% of N-P-K + remineralizer + Bacillus spp.; T6: 75% of N-P-K + Azospirillum spp.; T7: 75% of N-P-K + Bacillus spp. The soil fauna was sampled two times of the year using pitfall traps, and soil samples were collected at the same points for explanatory variables (chemical and microbiological attributes of the soil). The diversity of groups varied between the collection times, and the most frequent were Collembola, Formicidae, and Acari. The use of remineralizer favored the diversity of groups and the establishment of Collembola populations compared to treatments with conventional fertilizer.